Antioxidant capacity: concepts, quantification methods and use for tropical fruits and derived products characterization - Vázquez-Ovando, Alfredo; Mejía-Reyes, José David; García-Cabrera, Karina Elizabeth; Velázquez-Ovalle, Gamaliel (Revista Colombiana de Investigaciones Agroindustriales, 2022)
Antioxidant capacity has become a widely demanded feature in actually foods. The knowledge of the molecules that contribute this activity, as well as the natural foods where they can be found, provides information for the correct use of these important substances. However, even today, methods for measuring antioxidant capacity in vitro remain poorly unified. Although there are at least three universally used methods, the units in which the results are expressed are heterogeneous, which makes accurate comparison between samples of a similar nature somewhat difficult. This review includes a review of basic aspects of antioxidant capacity, with an emphasis on the molecules responsible for such activity and the methods available to quantify it. Additionally, given that foods of plant origin are the main natural source of antioxidant compounds, a brief review is made of studies that quantify the antioxidant capacity of tropical fruits and their products or co-products.